Use of fly-ash geopolymer incorporating ground granulated slag for stabilization of kaolin clay cured at ambient temperature - Abdullah, H.; Shahin, Mohamed; Sarker, Prabir (Spinger, 2018)
This paper focuses on stabilisation of kaolin clay at ambient temperature using fly-ash based geopolymer incorporating ground granulated blast-furnace slag (GGBFS). Comprehensive experimental programme was conducted including soil plasticity, compaction, unconfined compressive strength, durability and leaching. These tests were followed by a microstructural analysis using scanning electron microscopy (SEM) technique. An optimisation study using several combinations of geopolymer ingredients was performed, and the role of GGBFS in enhancing the geopolymer-stabilised clay was evaluated. The results indicated that introducing partial replacement of class (F) fly-ash by GGBFS assists, when synthesised in certain ratios, in achieving strength properties of geopolymer-stabilised clay comparable to those of cement stabilised clay. Although a small percentage of geopolymer can improve the soil strength, a larger amount was essential to enhance the wetting–drying durability performance. Under freezing–thawing conditions, low durability performance was detected indicating retardation in the geopolymer reaction at low temperature. For simulated water infiltration, leaching of the activator from geopolymer-stabilised clay was a minor concern in relation to the gel formation and long-term strength gain. Finally, SEM results clearly demonstrated a clay fabric modification attributed to the inter-particle contacts and the corresponding bonding due to the gel formation and hardening.